A Systematic Literature Review on Strenghtening Nationalism Character in Madrasah Ibtidaiyah - Amilussolikha, Dian; Lutfiyah, Diana; Sari, Dini Ratna; Sandrina, Inas; Romin, Reny Muk; Na'imah, Safira Lulu (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
This study aimed to construct a structured knowledge map regarding strategies for strengthening nationalism among students in Madrasah Ibtidaiyah (MI), a level of education uniquely combining moderate Islamic values with a nationalistic spirit. Employing the Systematic Literature Review (SLR) method, the research analyzed 11 articles published between 2021 and 2025, selected from an initial pool of 708 documents found across various scientific databases. The findings confirm that fostering nationalism in MI is achieved through three crucial pathways: (1) Classroom Learning by integrating national values into the curriculum, methods, and teaching materials; (2) Extracurricular Activities such as Scouting and Junior Police; and (3) School Culture, developed through planned programs, teacher role models, and systematic character management. This resulting knowledge map offers a vital conceptual foundation for educators and policymakers to design effective, context-appropriate strategies for national character building in MI students.